2007
DOI: 10.1007/s11258-007-9392-8
|View full text |Cite
|
Sign up to set email alerts
|

Iberian–Balearic fern regions and their explanatory variables

Abstract: This article delineates the compositional regions present in the Iberian-Balearic fern flora and compares these regions to previously proposed biogeographic units. It also assesses the extent to which environmental variables could explain the regions and the fern species richness gradients found within them. A combination of 40 previously published and new maps were used to compile the distribution of 123 pteridophytes on a 50 9 50 km UTM grid. Cluster analysis of the resulting 257 squares was used to classify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 57 publications
(70 reference statements)
0
25
0
1
Order By: Relevance
“…evidence supports this prediction and shows that the qualitative shape of the heterogeneity-diversity relationship may vary among different groups of organisms in the same region (20), within the same group of organisms among different regions (21), and within the same group of species and the same region when the data are analyzed at different scales (22). Furthermore, Tamme et al (23) recently showed that negative effects of habitat heterogeneity on species richness are significantly more common at small spatial scales, a finding fully consistent with our simulations (Fig.…”
mentioning
confidence: 52%
“…evidence supports this prediction and shows that the qualitative shape of the heterogeneity-diversity relationship may vary among different groups of organisms in the same region (20), within the same group of organisms among different regions (21), and within the same group of species and the same region when the data are analyzed at different scales (22). Furthermore, Tamme et al (23) recently showed that negative effects of habitat heterogeneity on species richness are significantly more common at small spatial scales, a finding fully consistent with our simulations (Fig.…”
mentioning
confidence: 52%
“…The primary cause underlying this relationship is accepted to be the decrease in the length of the growing season and in vegetation productivity with altitude, which determines a lower number of plant species being able to colonise the highest altitudinal ranges. However, several authors found the contrary phenomenon in the Iberian Peninsula (Castro-Parga et al, 1996;Lobo et al, 2001;Moreno-Saiz and Lobo, 2008), arguing that, under a Mediterranean climate, the climatic conditions in the upper mountain areas are not constraining biodiversity, but on the contrary, are the extreme temperatures and low precipitations occurring at lower altitude which, through hydric stress, might limit plant productivity and diversity. The presence of mountains has also been suggested to be a potential surrogate of many factors that might influence positively plant species richness (see Vetaas and Ferrer-Castán, 2008), like the increase in surface area, the higher geological heterogeneity, or its role as refuge during the last glacial periods.…”
Section: Relationships Among Explanatory Variables and Forest Biodivementioning
confidence: 99%
“…In this sense, distribution patterns of the vascular flora (e.g. Rivas-Mart ınez et al, 2002;Moreno Saiz & Lobo, 2008;Moreno Saiz et al, 2013), and in particular of endemic flora (e.g. Rivas Mart ınez et al, 1997; Garc ıa Barros et al, 2002;Santa Anna Del Conde et al, 2009;MedinaCazorla et al, 2010;Gonz alez-Orozco et al, 2013) has often been used to describe biogeographical schemes.…”
Section: Introductionmentioning
confidence: 99%